История возникновения и развития хозяйственного судопроизводства в Украине - Butyrskyi, Andrii (Legea si viata, 2013)
In article the history of development of economic legal proceedings in Ukraine is investigated. For completeness of research the history of formation of commercial vessels in Europe, and also experience of pre-revolutionary Russia is analysed. The author offered a periodization of history of creation and development of economic legal proceedings, is allocated the main lines of each stage. The special attention is paid to the Soviet period of development of the state arbitration as at this particular time were laid the foundation for economic vessels which in Ukraine solve today economic disputes. Also in article it is analysed approaches of scientists to the legal nature of the State arbitration that allowed to comprehend value of this body in the solution of economic disputes. В статье исследована история развития хозяйственного судопроизводства на Украине. В целях полноты исследования проанализирована история становления коммерческих судов в Европе, а также опыт дореволюционной России. Автором предложена периодизация истории создания и развития хозяйственного судопроизводства, выделено основные черты каждого этапа. Особое внимание уделено советскому периоду развития государственного арбитража, поскольку именно в это время были заложены основы хозяйственных судов, которые сегодня в Украине решают хозяйственные споры. Также в статье проанализированы подходы ученых к правовой природе Государственного арбитража, что позволило осмыслить значение данного органа в решении хозяйственных споров.
The history of the emergence and development of economic legal proceedings in Ukraine
Keywords: комерційний суд; арбітражні комісії; державний арбітраж; господарський суд; господарський спір; господарське судочинство; commercial court; arbitration commissions; state arbitration; economic court; economic dispute